Evaluation of diversion channel capacity using flood hydrodynamic modeling - Alahmadi, F. (CRC Press/Balkema, 2016)
Flash flood in arid regions are rare but destructive, the capacity of Wadi Bathan ephemeral diversion channel with 10.3 km length in Madinah, Western Saudi Arabia is evaluated using coupled 1D/2D flood hydrodynamic modeling. InfoWorks Integrated Catchment Modeling (ICM) software is used and aerial LiDAR data with 4 points/m2 resolution is utilized for automatic extraction of 1D cross sections and 2D floodplain areas. The synthetic flood hydrograph for 100-year return period is computed using HEC-HMS software and used as inflow to the flood hydrodynamic model. Results of flood inundation mapping showed at least two flood prone areas, and more detailed flood characteristics are computed such as flood extent depth, and surface water profiles. This study showed the importance of flood hydrodynamic modeling and LiDAR data as powerful tools in flash flood simulation and ephemeral channel evaluation in arid regions.